Thinking About Global Warming: Effect of Policy-Related Documents and Prompts on Learning About Causes of Climate Change. Issue 4 (19th May 2017) - Blaum, Dylan; Griffin, Thomas D.; Wiley, Jennifer; Britt, M. Anne
Abstract : We examined students' understanding of the causes of a scientific phenomenon from a multiple-document-inquiry unit. Students read several documents that each described causal factors that could be integrated to address the given writing task of explaining the causes of change in average global temperature. We manipulated whether the document set included a document that took a position on climate change policies and whether a reading/writing prompt focused only on understanding the causes ("explain how and why recent temperature changes are occurring") or also included a solution-related addendum ("and what we can do about it"). The results suggest that including a policy-related document can lead to poorer learning outcomes for the causes of climate change, with evidence that students focused on policy in lieu of, rather than in relation to, a causal understanding of the issue.